2002
DOI: 10.1590/s0100-204x2002001200016
|View full text |Cite
|
Sign up to set email alerts
|

Movimentação de metais pesados em Latossolo adubado com composto de lixo urbano

Abstract: Em experimento realizado no campo, nos anos agrícolas 1996/97 e 1997/98, em Latossolo Amarelo distrófico, cultivado com cana-de-açúcar, avaliou-se o efeito de aplicações sucessivas de composto de lixo urbano sobre a movimentação, em profundidade, dos metais Cd, Cr, Cu, Ni, Pb e zinco. No primeiro ano agrícola, além do tratamento testemunha, o composto de lixo foi aplicado nas doses de 20, 40 e 60 Mg ha-1 (base seca). No segundo ano, o composto foi reaplicado nas doses de 24, 48 e 72 Mg ha-1. Em relação aos met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…The non-detection of Cu in surface waters was not expected, since Cu is found in inorganic fertilizers, and these are applied in agricultural areas on a regular basis. The nondetection of this element may be due to the low mobility of Cu in the soil, accumulating on the surface thereof (OLIVEIRA et al, 2002). Gonçalves et al (2015) also reported non-detection of Cu in the waters of Cuiaba and Sao Lourenco rivers (Class 2), whose basins have agricultural activities similar to those of the present study.…”
Section: First Step -Monthly Monitoringsupporting
confidence: 71%
See 1 more Smart Citation
“…The non-detection of Cu in surface waters was not expected, since Cu is found in inorganic fertilizers, and these are applied in agricultural areas on a regular basis. The nondetection of this element may be due to the low mobility of Cu in the soil, accumulating on the surface thereof (OLIVEIRA et al, 2002). Gonçalves et al (2015) also reported non-detection of Cu in the waters of Cuiaba and Sao Lourenco rivers (Class 2), whose basins have agricultural activities similar to those of the present study.…”
Section: First Step -Monthly Monitoringsupporting
confidence: 71%
“…It can also be found in phosphate fertilizers, according to Santos and Jesus Bonfim (2014). It has low mobility in the soil (OLIVEIRA et al, 2002), accumulating on its surface. However, this river has native marginal forest throughout its course, which serves as a barrier to sediment input arising from the basin soils, reducing erosion of margins, with exception to its source (ANDRIETTI et al, 2016).…”
Section: Pointmentioning
confidence: 99%
“…Os metais pesados podem expressar seu potencial poluente diretamente sobre os organismos do solo, pela disponibilidade às plantas e contaminação de águas superficiais, via erosão do solo, e de águas subsuperficiais, por movimentação vertical descendente no perfil do solo (Oliveira et al 2002). A possível contaminação por metais pesados, em aquíferos próximos a áreas de deposição de resíduos siderúrgicos, dependerá, dentre numerosos fatores, da concentração e solubilidade destes elementos presentes nos resíduos, da quantidade de resíduos aplicada, da precipitação pluviométrica e de sua interação com a fase sólida do solo (Amaral Sobrinho et al 1998).…”
Section: Key-wordsunclassified
“…12 Santos et al 13 reported that the use of compost from the same community collected at different times and from different solid waste treatment plants might affect differently soil properties, such as the pH. The increase of compost dose might result in an inadequate soil pH for lettuce cultivation.…”
Section: Introductionmentioning
confidence: 99%